United States: Shadow WTO Agricultural Domestic Support Notifications - Blandford, David; Orden, David (International Food Policy Research Institute, 2008)
This paper examines past and proposed U.S. domestic support in light of current and potential World Trade Organization (WTO) constraints. It provides a brief review of U.S. farm policies since the Uruguay Round WTO agreements went into effect, including a synopsis of the new Food, Conservation, and Energy Act of 2008. It examines the United States’ notifications to the WTO of domestic support from 1995 to 2005 and provides a preliminary notification estimate for 2006. Green-box (non trade-distorting) expenditures for domestic nutrition programs dominate the total dollar values notified by the United States. The main notified components of the U.S. support policies for agricultural producers include fixed direct payments, disaster assistance, and environmental payments in the green box; market price supports for dairy and sugar and substantial price-linked, loan-rate-related subsidy expenditures in the product-specific aggregate measure of support (AMS) category; and non product-specific support notified as de minimis, including crop market loss assistance payments, countercyclical payments, and crop and revenue insurance subsidies. The United States’ notification of total AMS has not exceeded the Uruguay Round commitment of $19.1 billion. It would have exceeded this amount in some years if the fixed direct payments were included in the AMS, an issue arising in challenges to the U.S. notifications. This paper discusses other subsidies that may be underreported, misclassified, or omitted, including the blender tax credits and mandates related to ethanol production that have been largely outside the disciplines of the Uruguay Round Agreement on Agriculture. It also provides an assessment of projected U.S. support through 2014. Under the Uruguay Round rules, there is essentially no constraint on U.S. policies if high prices projected in mid 2008 are realized. The WTO constraints are tighter if the proposed Doha Development Agenda disciplines of July 2008 are agreed upon. In that case, under the projected prices, the United States would still have some leeway to increase expenditures under its commitments. Thus, if the economic environment that is foreseen in the projections proves correct, the United States would be able to adapt to the proposed Doha Round domestic support modalities by making only modest adjustments in its policies, although product-specific support for sugar, cotton, or other products could face constraints. Large payments under a new revenue guarantee program in the 2008 farm bill could violate the U.S. commitments, even if prices remain high enough not to trigger traditional countercyclical or loan-rate payments.